Synthesis and characterization of superoleophobic fumed alumina nanocomposite coated via the sol-gel process onto ceramic-based hollow fibre membrane for oil-water separation. Issue 18 (15th September 2021) - Raji, Yusuf Olabode; Othman, Mohd Hafiz Dzarfan; Sapiaa Md Nordin, Nik Abdul Hadi; Adam, Mohd Ridhwan; Mohd Said, Khairul Anwar; Ismail, Ahmed Fauzi; Rahman, Mukhlis A.; Jaafar, Juhana; Farag, Twibi Mohamed; Alftessi, Sabeer Abdulhamid
Abstract: Oily wastewater treatment is a global challenge due to the substantial amount of effluent resulted from many industrial and domestic activities. To overcome the challenge of using existing treatment approach and fouling, superoleophobic coatings were fabricated. In this study, a superoleophobic membrane surface was obtained using the sol-gel technique with perfluorooctanoate (PFO), poly (diallyl dimethylammonium chloride) (PDADMAC), and nanoparticles as complex-polymer nanocomposites. The effects of coating cycles on the surface structure, chemical properties, surface chemistry, and oleophobicity of the surface were examined using field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and oil contact angle measurement. The results showed that the coated layer successfully adhered to the substrate surface. However, the chemical stability with respect to oil contact angle (OCA) revealed a decline at pH 7 and pH 9 and maintained stability at pH 3. Besides, oil flux at 63.0 L/m 2 . h was achieved for PDADMAC-Al2 O3 /44 wt% PFO and the highest separation efficiency of 98% was obtained. Furthermore, the oil rejection decreases as the oil concentration increases from 1 to 3 g/L. OCA of 155° was obtained after 5 coating cycles. Apart from mitigating substrate fouling, the superoleophobic and superhydrophilic coating can be applied to a ceramic-based hollow fibre membrane and efficiently used for the separation of oil from oily wastewater. Graphical abstract: Image 1